Handbook on entrepreneurship research : an interdisciplinary survey and introduction - Ács, Zoltán J.; Audretsch, David B. (International handbook series on entrepreneurship ;, 2010)
Since its original publication in 2003, the Handbook of Entrepreneurship Research has served as the definitive resource in the field, bringing together contributions from leading scholars in such disciplines as management, finance, economics, policy, sociology, and psychology to present a holistic, multi-dimensional approach. This new edition, fully revised and updated, and including several new chapters, covers all of the primary topics in entrepreneurship, including entrepreneurial behavior, risk and opportunity recognition, equity financing, business culture and strategy, innovation, and the impact of entrepreneurship on economic growth and development. Featuring an integrative introduction, extensive literature reviews and reference lists, the Handbook will continue to serve as a roadmap to the continually evolving and dynamic field of entrepreneurship."The Handbook of Entrepreneurship Research provides doctoral students with a broad yet solid introduction to the field, and established scholars with an overview that is otherwise very hard to obtain. It is a must read for every academic who is serious about entrepreneurship." Per Davidsson, The Jönköping International Business School "Acs and Audretsch have assembled a virtual who's who list of researchers in the fledgling field of entrepreneurship. Even more usefully, the Handbook also includes reviews of the vast array of work closely related to entrepreneurship that has appeared primarily in economics, psychology and sociology journals; despite their relevance, locating these studies can prove difficult as their authors frequently do not focus on the implications of their research for entrepreneurship." Olav Sorenson, University of California, Los Angeles.